Analisis Kesalahan Berbahasa Bidang Fonologi Pidato Presiden Jokowi pada UOB Economic Outlook 2023 - Ira Siti Nurapiatul Z; Irwan Siagian (Jurnal Ilmiah Wahana Pendidikan, 2023)
The research aims to describe the pronunciation errors in the field of phonology in President Joko Widodo's speech at the UOB Economic Outlook 2023 event. The research method used is qualitative descriptive. The data source is a video from the social media platform YouTube. The data for this research is the president's speech at the UOB Economic Outlook 2023. The data collection technique involves careful listening and note-taking to obtain relevant research data, followed by explaining and categorizing the phonological errors found. Content analysis is employed as the analysis technique. The findings from the research on President Joko Widodo's speech at the UOB Economic Outlook 2023 event are as follows: 1) There are omissions of vowel/diphthong phonemes. 2) There are changes in vowel and consonant phonemes. 3) There are reductions in vowel and consonant phonemes.